Experimental Investigation of a Novel Blast Wave Mitigation Device - Zhenbi Su; Wen Peng; Zhaoyan Zhang; George Gogos; Reed Skaggs; Bryan Cheeseman; Chian Fong Yen (Shock and Vibration)
A novel blast wave mitigation device was investigated experimentally in this paper. The device consists of a piston-cylinder assembly. A shock wave is induced within the cylinder when a blast wave impacts on the piston. The shock wave propagates inside the device and is reflected repeatedly. The shock wave propagation process inside the device lengthens the duration of the force on the base of the device to several orders of magnitude of the duration of the blast wave, while it decreases the maximum pressure over an order of magnitude. Two types of experiments were carried out to study the blast wave mitigation device. The first type of experiments was done with honeycomb structures protected by the blast wave mitigation device. Experimental results show that the device can adequately protect the honeycomb structure. A second type of experiments was done using a Hopkinson bar to measure the pressure transmitted through the blast wave mitigation device. The experimental results agree well with results from a theoretical model.